On the development of past habitual from iterative in Lithuanian - Pakerys, Jurgis (Baltistica, 2017)
Lithuanian has regular past habitual forms with the suffix -dav-, which can be explained as an originally iterative suffix -dau- restricted to the past tense (Fraenkel 1936). Dialectal and Old Lithuanian, in addition to -dav-, also feature habituals with the suffixes -lav- and -dlav-, which could have followed the same path of development (Fraenkel 1936), as evidenced by a number of diverse languages (Bybee et al. 1994). Using an electronic edition of Lietuvių kalbos žodynas (The Dictionary of Lithuanian) as the data source, a limited number of possible iteratives with -dau- and other related suffixes were found, which has led to two main conclusions. (1) Habituals were restricted to the past tense before the appearance of the first written Lithuanian texts (mid-16th c.) and the present and the infinitive stems went out of use. If this had not been the case, more corresponding verbal formations should have remained. (2) Iteratives with the habitual-to-be suffixes had to be productive to some extent in the dialects, which grammaticalized them as past habituals. If these formations had been productive in all dialects of Lithuanian, more iteratives should have been found in the areas that did not grammaticalize them as past habituals. It is also suggested that the form-frequency correspondence principle (Haspelmath 2008, 2014, 2017) should have operated in the formation of the Lithuanian habitual. Longer suffixes were chosen to mark habitual situations as a less frequent subtype of iterative situations and habitual forms were restricted to the past tense because habituality is one of the default (more frequent) readings of the present and hence the habituals in the past tend to be marked explicitly (Bybee et al. 1994).